IMPLEMENTASI UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG TINDAK PIDANA KORUPSI PERSPEKTIF KEPASTIAN HUKUM (Jurnal Hukum Mimbar Justitia, 2021)
Efforts and protection for all nations and bloodshed through existing legal instruments are absolute things, there is no meaning in the words "efforts to protect all nations and bloodshed" if it turns out that there is still suffering felt by the people in the form of an imbalance in their rights. economic rights that reflect the welfare of all Indonesian people. In other words, with the formulation of “Formil Offenses”, even though the proceeds of corruption have been returned to the state, the perpetrators of criminal acts of corruption can still be brought to court and can still be convicted (Article 2 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of No Corruption). The similarities between these laws, both Law No. 3 of 1971 and Law No. 31 of 1999, both “do not contain a firm evidentiary system, compared to Law No. 20 of 2001 concerning the Eradication of Non-Criminal Corruption. In Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, the offense is formulated materially, so that in its investigation, it must be able to prove a causal relationship between unlawful acts and losses that have occurred as a causality. while the definition of a material offense itself is an offense whose consequences are prohibited by law.Keywords: Formal Offenses, Corruption, Legal Certainty, Criminal.